Intention to use m-banking application: an empirical study in Ho Chi Minh City - Le-Hoang, Phuong Viet (2021)
The research aims to explore, measure, and analyze factors affecting the intention to use Mobile Banking (M-Banking) of customers in Ho Chi Minh City. The author conducts a convenient sampling, including 600 participants. The method of the research is the Exploratory Factor Analysis (EFA) and a multiple regression model. The results show that there are six factors such as perceived ease to use (EU), perceived usefulness (PU), trust (TR), expected performance (PE), social influence (SI), Facilitating condition (FC) affect the adoption of M-Banking. In which, Facilitating condition is the most influential factor, and expected performance is the least influential factor. Also, this study proposes some recommendations to develop an M-Banking application to help customers gain more insight into the bank as well as actively select the M-Banking application as a reliable transaction method.